(untitled) (Fiep Bulletin - online, 2011)
Krukutu The village is situated in the metropolitan region of Sao Paulo in the south of the county in the District Administrative Parelheiros in the neighborhood Dam. Much of the area of the village is on the banks of the Billings Reservoir, an important area of preservation of water sources. And therefore objectives of this work, a study on the Environmental Public Policies in Brazil, in São Paulo and São Paulo, and the reality of these policies in the Village Guarani Krukutu. Even though the Village in important conservation units (UC), and each having its policies for the preservation and maintenance of traditional peoples, and with the principles of maintaining the livelihood of these people, today the village community can be seen in serious environmental problems, health, social. Yet communities retain their nhandereko (lifestyle). It is up to public policies on environmental issues meet with his role as an integrator and manager of conflict, which is not seen in the area. integrator and manager of conflict, which is not seen in the area.